(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article serves as an insightful exploration into the foundational principles of Comparative Linguistics, a discipline crucial for unraveling the historical and structural aspects of languages. Beginning with an overview of historical linguistics, the article delves into the meticulous methodologies employed in establishing language families and genetic classifications. It emphasizes the importance of sound correspondences and phonological changes, showcasing how linguists use these elements to reconstruct ancestral forms of words. The article concludes by highlighting the relevance of dialectology in studying regional language variations. In essence, this annotation encapsulates the comprehensive exploration of Comparative Linguistics, providing a valuable resource for readers interested in the intricate web of connections that bind languages throughout history.